State Dementia Plans and the Alzheimer's Disease Movement: Framing Diagnosis, Prognosis, and Motivation. (July 2017) - Arbogast, Charlotte E.; Welleford, E. Ayn; Netting, F. Ellen
An interpretive analysis of 38 state dementia plans compares similarities and differences in diagnostic framing (problem identification/trends/issues), prognosis framing (addressing the problem), and motivational framing (calls for action) across plans. In framing diagnosis, only 6 plans used dementia alone in their titles. In framing prognosis and the subsequent call to action, state plans were consistent in their dire prognostications about the progressive and fatal consequences of the disease with a primary focus on the cost. Motivational language mirrored that of the Alzheimer's Disease (AD) Movement, from raising awareness to using inflammatory words to incite action. The language used set up the frame for clinical interventions that may not distinguish between types of dementia and could undercut the provision of person-centered care, shifts the victimization focus from persons with AD to caregivers and ultimately the state, and may subintentionally reflect cultural biases.